Implementing the evidence translation-based resilience care model on family caregivers of stroke patients: a best-practice implementation project. Issue 4 (14th December 2022) - Chang, Cheng-Yu; Wu, Fu-Mei; Lin, Hsu-Nu; Ho, Lun-Hui; Su, Jui Yuan; Liang, Ching-Chuan; Yang, Shu-Hua; Huang, Tzyy-Jen; Mu, Pei-Fan
ABSTRACT: Objectives: The aim of this project was to promote for the family caregivers of stroke patients the resilience evidence translation care model in the community. Introduction: Stroke is the main cause of disability among many patients with chronic diseases. Resilience helps family caregivers facing the consequences of adversity and stress to have a positive outcome. Methods: The study utilized clinical audit strategies under the JBI Practical Application of Clinical Evidence System module. Three audit criteria for the caregivers of stroke patients were considered. A preimplementation audit was conducted with eight nurses and 30 caregivers to measure compliance between current practice and best practice. From that audit we identified barriers and facilitators to practice change by undertaking a Getting Research into Practice analysis. A postimplementation audit was conducted using the same number of samples at 8 weeks for the caregivers to evaluation, and the outcomes using follow-up audit. Results: The three criteria showed an improvement: nurses who received education about resilience care protocols, criterion 1 from 0 to 100%, criterion 2 from 0 to 100%, criterion 3 from 0 to 90%. The results showed that the average resilience of caregivers increased from 17.47 (SD ± 1.94) to 18.33 (SD ± 1.54). The resilience scale of pretest and posttest scores were significantly improved ( P  ≤ 0.001). Conclusion: The implementation of best practice for enhancing resilience of the family caregivers of stroke patients on the resilience evidence translation care model: a best practice implementation project in community settings is possible. The results indicate that evidence-based practice is an effective method for enhancing the resilience of family caregivers. The strategies contributed to the success of this project, such as scenario simulation education, Objective Structured Clinical Examination, regular weekly audits, and collaboration with project leaders when carrying out caregiver case discussion during clinical practice.